Report of the Committee on Technical - Consultancy Services - Planning Commission (Planning Commission, 1970)
The services rendered by technical consultants can be classified into (1) Project Planning, (2) Project Designing, (3) Project Implementation and (4) Project Evaluation. The professional engineers undertaking technical services can be broadly categorised as (a) consulting engineers(b)- process engineers and (c) contracting engineers.
Government of India Planning Commission